Nanostructures: Highly Scalable, Closed‐Loop Synthesis of Drug‐Loaded, Layer‐by‐Layer Nanoparticles (Adv. Funct. Mater. 7/2016). (February 2016) - Correa, Santiago; Choi, Ki Young; Dreaden, Erik C.; Renggli, Kasper; Shi, Aria; Gu, Li; Shopsowitz, Kevin E.; Quadir, Mohiuddin A.; Ben‐Akiva, Elana; Hammond, Paula T.
Abstract : P. T. Hammond and co‐workers present a technique that uses tangential flow filtration for rapid, high‐yield preparation of biomedically relevant layer‐by‐layer nanoparticles. Diverse nanoparticles with diameters ranging from 40 to 150 nm were prepared from polystyrene, mesoporous silica, and drug‐loaded liposomal cores. Using this technique, nanoparticles could be coated with a broad range of polyelectrolytes including polysaccharides, polypeptides, and synthetic polymers. The prepared nanoparticles are suitable for long‐term storage under refrigerated conditions, as well as for lyophilized, room‐temperature storage.